Post Disaster Reconstruction after 2015 Gorkha Earthquake: Challenges and Influencing Factors - Sharma, Keshab; KC, Apil; Subedi, Mandip; Pokharel, Bigul (Journal of the Institute of Engineering, 2018)
The Gorkha earthquake on April 25, 2015 has significantly affected the livelihood of people and overall economy in Nepal, causing severe damage and destruction in central Nepal including nation's capital. 800 thousand buildings were affected leaving 8 million people homeless. Challenge of reconstruction of optimum 800 thousand houses is arduous for Nepal Government in background of its turmoil political scenario and weak governance apart from its difficult geographical terrain. Albeit, with significant number of stakeholders involved in the reconstruction process, no appreciable progress has seen to the ground till date, which is reflected over the frustration of affected people. In order to identify factors hindering timely and quality reconstruction, this research has brought basic arguments and ideas prospected by different actors involved in the process. Methodology of the study is comprised with semi structured interviews with social mobilizers, engineers working in the field, and affected people, group discussion, field observations and regular follow-up of the incidents through national newspapers and discussion forums. This study concludes that inaccessibility, absence of local government, weak governance, weak infrastructures, lack of preparedness, knowledge gap and manpower shortage etc. are the key challenges of the reconstruction after 2015 earthquake in Nepal. Good governance, integrated information, addressing technical issues, public participation along with short term and long term strategies to tackle with technical issues are highlighted as some imperative factors for timely and quality reconstruction in context of Nepal. Journal of the Institute of Engineering, 2018, 14(1): 52-63